An experiment of Kartalin liniment for palmar-plantar form psorias and other keratodermias - V. S. Dmitruk (Бюллетень сибирской медицины, 2011)
Keratodermias can be isolated or can be a part of syndromes typical for other dermatological deceases. Investigation of clinical effectiveness of Kartalin liniment in complex therapy of palmar-plantar keratodermias was held with a group of 26 patients with different clinical variants of the deceases. Besides local treatment, the patients got systematic therapy corresponding to the standards of medical treatment for each nogological form.For estimation of clinical effectiveness of the suggested complex of general and local arrangements there was done a calculation of the number of days spent in hospital white curing keratodermias. This showing made up 23 days in the examined group and positive clinical dynamics in the control group has been noticeable sense 33,7 day.